Important characteristics and realization ways of wisdom mine - HE Min (Gong-kuang zidonghua, 2018)
Current status and problems of mine informatization construction were analyzed. Important characteristics of wisdom mine which were different from the ones of automation mine, informatization mine and digitalized mine were summarized, namely thorough perception, deep interconnection and high intelligence. Realization ways of wisdom mine were proposed, which include making technical specification and standard of wisdom mine, implementing complete digitalization of mine information, researching and promoting advanced intelligent technology and equipment, and developing wisdom decision application.